Promoting Cyberspace Governance Through Technical Standards - Sun Ruochen; Zhang Lei; Li Linzhe; An Da; Cui Yong (中国工程科学, 2024)
Strengthening the cyber industry is a major strategic goal of China in the new era of development. It is also crucial for the modernization of national governance system and capabilities. Technical standards serve as key tools for achieving consensus and fostering cooperation, making them vitally important to the construction of a shared cyberspace community and the establishment of a comprehensive governance system. This study examines the current international development in cyberspace governance driven by technical standards, focusing on key elements such as paradigmatic nature, multi-sourcing, legal integration, patent-related issues, and network effects. We systematically summarize China’s experiences, challenges, and existing issues in this area, proposing corresponding thoughts, overall objectives, and strategic paths. In response to issues such as China’s weak core technical capabilities in cyberspace, insufficient international discourse power over technical standards, uncoordinated legislation on standards content, urgent need for improving standard-essential patent systems, and suboptimal network effects of technical standards, this study proposes developmental suggestions. These include targeting technical standards in key areas, promoting diversification of entities responsible for technical standards development, providing vocational training and talent education related to technical standards, strengthening patent management and intellectual property protection, emphasizing the popularization and adoption of technical standards, as well as advancing international cooperation and standardization. The aim is to enhance the effectiveness of standardized governance, elevate the level of national standardization, and promote the progress of cyberspace governance in China.